![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
2个回答
展开全部
解题思路:1/n(n+1)(n+2)
=1/2{[(n+2)-n]/[n(n+1)(n+2)]}
=1/2[1/n(n+1)-1/(n+1)(n+2)]
所以原式=1/2[(1/1x2-1/2x3)+(1/2x3-1/3x4)+(1/3x4-1/4x5)+……+(1/20x21-1/21x22)]
=1/2(1/1x2 -1/2x3+1/2x3 -1/3x4+1/3x4 -1/4x5+……+1/20x21-1/21x22)
=1/2(1/1x2-1/21x22)
=1/2×230/462
=115/462
祝你好运
=1/2{[(n+2)-n]/[n(n+1)(n+2)]}
=1/2[1/n(n+1)-1/(n+1)(n+2)]
所以原式=1/2[(1/1x2-1/2x3)+(1/2x3-1/3x4)+(1/3x4-1/4x5)+……+(1/20x21-1/21x22)]
=1/2(1/1x2 -1/2x3+1/2x3 -1/3x4+1/3x4 -1/4x5+……+1/20x21-1/21x22)
=1/2(1/1x2-1/21x22)
=1/2×230/462
=115/462
祝你好运
展开全部
解题思路:1/n(n+1)(n+2)
=1/2{[(n+2)-n]/[n(n+1)(n+2)]}
=1/2[1/n(n+1)-1/(n+1)(n+2)]
所以原式=1/2[(1/1x2-1/2x3)+(1/2x3-1/3x4)+(1/3x4-1/4x5)+……+(1/20x21-1/21x22)]
=1/2(1/1x2 -1/2x3+1/2x3 -1/3x4+1/3x4 -1/4x5+……+1/20x21-1/21x22)
=1/2(1/1x2-1/21x22)
=1/2×230/462
=115/462
=1/2{[(n+2)-n]/[n(n+1)(n+2)]}
=1/2[1/n(n+1)-1/(n+1)(n+2)]
所以原式=1/2[(1/1x2-1/2x3)+(1/2x3-1/3x4)+(1/3x4-1/4x5)+……+(1/20x21-1/21x22)]
=1/2(1/1x2 -1/2x3+1/2x3 -1/3x4+1/3x4 -1/4x5+……+1/20x21-1/21x22)
=1/2(1/1x2-1/21x22)
=1/2×230/462
=115/462
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询